2015
DOI: 10.1007/s00213-015-3954-6
|View full text |Cite
|
Sign up to set email alerts
|

The subchronic phencyclidine rat model: relevance for the assessment of novel therapeutics for cognitive impairment associated with schizophrenia

Abstract: The multi-site study confirmed that scPCP impaired NOR and ASST only and demonstrated the reproducibility and usefulness of the touchscreen approach. Our recommendation, prior to testing novel therapeutics in the scPCP model, is to be aware that further work is required to understand the neurochemical changes and specificity of the cognitive deficits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 173 publications
0
20
0
Order By: Relevance
“…Certain brain regions and neurotransmitter systems including hippocampus, striatum, basal forebrain, cerebral cortex, and cerebellum play an important role in the MWM performance of rodents [33]. Different studies showed that glutamatergic NMDA receptor activity is crucial for spatial learning and memory, and antagonists of these receptors revealed cognitive impairments on the MWM test in rodents [34][35][36]. Our results indicated that sub-chronic MK-801 administration induced persistent learning deficits in the acquisition period at all of the 4 days and memory defect in the probe test.…”
Section: Discussionmentioning
confidence: 99%
“…Certain brain regions and neurotransmitter systems including hippocampus, striatum, basal forebrain, cerebral cortex, and cerebellum play an important role in the MWM performance of rodents [33]. Different studies showed that glutamatergic NMDA receptor activity is crucial for spatial learning and memory, and antagonists of these receptors revealed cognitive impairments on the MWM test in rodents [34][35][36]. Our results indicated that sub-chronic MK-801 administration induced persistent learning deficits in the acquisition period at all of the 4 days and memory defect in the probe test.…”
Section: Discussionmentioning
confidence: 99%
“…The literature on the effects of subchronic NMDAR antagonism with phencyclidine (PCP) (considered a potential model of schizophrenia (Brigman et al, 2010a) is also equivocal. While early studies found reversal learning impairments with acute or subchronic PCP treatment in rodents (Abdul-Monim et al, 2007), more recent reports find no change (Brigman et al, 2009, Janhunen et al, 2015) or an improvement in late-stage reversal learning (Dix et al, 2010, Fellini et al, 2014, McAllister et al, 2015). As with other apparently discrepant data in the reversal literature, the potential for methodological variation to explain some of these differences should not be discounted.…”
Section: Neurochemical Modulation Of Reversalmentioning
confidence: 93%
“…The N-methyl-D-aspartate glutamate receptor (NMDA-R) is firmly implicated in normal physiological processes such as synaptic plasticity and learning along with being implicated in diseased and disordered states such as excitotoxicity and schizophrenia. Indeed, non-competitive NMDA-R antagonists are routinely used to model schizophrenia in rodents (Neill et al, 2014;Janhunen et al, 2015). Additionally, given the use of noncompetitive NMDA-R antagonists in humans as medical interventions (ketamine) and as drugs of abuse (phencyclidine; PCP), it is important to understand the neurophysiological effects of these drugs to find new clinical uses for existing drugs like ketamine and to design novel antipsychotic and antidepressant compounds with fewer side effects and greater therapeutic value.…”
Section: Introductionmentioning
confidence: 99%